SURGICAL VS. CONSERVATIVE MANAGEMENT OF ACUTE ACHILLES TENDON RUPTURE: A COMPARATIVE ANALYSIS OF FUNCTIONAL OUTCOMES AND RE-RUPTURE RATES - Weronika Justyna Skoneczna; Jakub Jan Woźniak; Lidia Mądrzak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Acute Achilles tendon rupture (AATR) is a frequent injury among physically active adults. Despite extensive research, the optimal management strategy (surgical versus conservative) remains controversial due to differences in re-rupture rates, complication profiles, rehabilitation protocols and patient-specific factors. While surgery has traditionally been favored for reducing re-rupture risk, advances in early functional rehabilitation have strengthened support for nonoperative treatment.Objective: This study aims to compare surgical and conservative management of AATR with respect to re-rupture rates, functional outcomes, complications and time to return to activity.Methods: A narrative comparative review was conducted using PubMed and PMC databases, including randomized controlled trials, cohort studies and meta-analyses published up to December 2025. Studies involving adult patients with AATR and reporting functional outcomes, complication rates and rehabilitation protocols with a minimum follow-up of approximately six months were included. Cadaveric and non-comparative studies were excluded.Results: Surgical treatment was associated with a lower re-rupture rate (3.7%) compared with conservative management (9.8%), but demonstrated higher rates of complications, particularly wound infection and nerve injury. Minimally invasive surgical techniques reduced complication risk while preserving efficacy. Functional outcomes such as range of motion, return to work or sport and patient-reported scores (e.g., ATRS) were comparable between treatment modalities when early mobilization and structured rehabilitation protocols were implemented.Conclusions: Surgical treatment provides a modest advantage in preventing re-rupture but carries an increased risk of complications. Conservative management with functional rehabilitation yields similar long-term functional outcomes. Treatment decisions should be individualized, incorporating patient characteristics, activity level and preferences. Further high-quality studies are needed to optimize rehabilitation strategies and refine treatment selection criteria.